Adjusting a mainstream weight management intervention for people with intellectual disabilities: a user centred approach - Liz Croot; Melanie Rimmer; Sarah Salway; Chris Hatton; Emma Dowse; Jacquie Lavin; Sarah E. Bennett; Janet Harris; Alicia O'Cathain (BMC, 2018)
Abstract Background People with intellectual disabilities (ID) may not be able to access and respond to uniformly delivered health interventions. Public bodies have a legal duty to make 'reasonable adjustments' to policies and practices to provide fair access and treatment for people with ID. This study aimed to identify adjustments to the Slimming World weight management programme to improve accessibility and assess acceptability and feasibility for this population. Methods This user-centred qualitative study was carried out with a steering group of people with ID (n = 4). Barriers and facilitators to using Slimming World were identified through interviews and focus groups with people with ID (n = 54), carers (n = 12) current members with ID (n = 8) and Slimming World group leaders (n = 11). Adjustments were made and their feasibility and acceptability were explored in a before-and-after mixed methods study where people with ID attended Slimming World for eight weeks. Participants (n = 9), carers (n = 7) and Slimming World group leaders (n = 4) were interviewed to explore their experiences of the adjustments. Participants were weighed at baseline then each week. Results Four key adjustments were identified and addressed by Slimming World who developed prototype Easy Read materials and a letter for carers. Six of the nine participants attended Slimming World for eight weeks and lost weight (1.4 kg to 6.6 kg, reduction in BMI between 0.5 and 1.7 kg/m2), indicating that the adjustments were feasible and acceptable. Two participants dropped out because they felt uncomfortable in a mainstream group and another left because they lacked control over food choice in their residential setting. Conclusions This user-centred approach identified reasonable adjustments that were feasible to implement. In a small uncontrolled feasibility study, people with ID were positive about the adjustments and lost weight. However, issues in the wider context of people's lives, such as obesogenic environments and concerns about joining mainstream groups, limited the acceptability of Slimming World even with these adjustments. These findings have important implications for policy and suggest that environmental and organisational level interventions are needed alongside those targeting individual behaviour to tackle the obesogenic environment in which many people with ID spend their time, in order to reduce inequalities associated with the consequences of obesity.